The (non-)translation of English-language, embedded social media quotes in Norwegian and Spanish online news texts: Effects of assumed levels of reader proficiency? - Greenall, Annjo; Aranda, Lucía (Meta, 2023)
In this article, we investigate journalist-translators’ strategies in dealing with English-language embedded social media quotes (ESMQs) in Norwegian and Spanish online news texts. Embedded social media quoting is a relatively new, but fast-growing phenomenon, which has yet to receive much scholarly attention. A few possible reasons for the (non-)translation of ESMQs in their surrounding main texts have been suggested in the hitherto scant literature, but one important hypothesis has not yet been introduced, namely that journalist-translators’ assumptions regarding the degree of English proficiency in their readers might influence their decisions regarding whether to translate (and how to translate). In this article, we present a comparison of the (non-)translation of 120 ESMQs in Norwegian vs. Spanish online news texts, which shows that there are in fact no significant differences in the rate of non-translation of these quotes, despite the fact that Norway and Spain are countries where English proficiency is assumed to be high vs. low, respectively. This means that assumed proficiency in the source language does not play the expected role in guiding journalist-translators’ decisions in our study, except if one can say that non-translation is chosen for two different reasons in the two groups: 1) a high degree of faith in the English proficiency of readers (in the Norwegian case), and 2) a low degree of confidence in one’s own English proficiency leading to translation avoidance (in the Spanish case). We conclude that qualitative research looking into various groups of journalist-translators’ motivations for (non)translation is needed.